2003
DOI: 10.1016/s0021-8502(02)00181-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-time measurement of bacterial aerosols with the UVAPS: performance evaluation

Abstract: This paper presents the results of the laboratory evaluation of the Ultraviolet Aerodynamic Particle Size Spectrometer, the novel instrument for real-time continues monitoring of bioaerosols. The main focus of this study was on evaluating selectivity, sensitivity, counting efficiency, and the detection limits of the UV APS.The tests were performed with two types of aerosols, bacterial (e.g., Bacillus sub ti/is spores or vegetative cells, and Pseudomonas fluorescens) and nou-bacterial (e.g., NaCl, latex, pepton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
97
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 29 publications
(32 reference statements)
3
97
0
Order By: Relevance
“…Schmit and Brody (1976) found that Neurospora crassa spores had low level of reduced cofactors, NADH and NADPH, compared with a high level for its mycelia. It was also shown that many non biological aerosols such as peptone water, broth or other materials, had strong fluorescent signals (Agranovski et al 2003a). Thus there is a need for a better understanding of these environmental factors and their effect on the instruments response to different bioaerosols.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmit and Brody (1976) found that Neurospora crassa spores had low level of reduced cofactors, NADH and NADPH, compared with a high level for its mycelia. It was also shown that many non biological aerosols such as peptone water, broth or other materials, had strong fluorescent signals (Agranovski et al 2003a). Thus there is a need for a better understanding of these environmental factors and their effect on the instruments response to different bioaerosols.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst a significant amount of work has been published regarding the application of the UVAPS to the aerosols carrying bacteria (Agranovski et al 2003a, Agranovski et al 2003b, only a very limited amount of work has been done on the fluorescence spectra of fungal spores and application of the UVAPS to detection of fungal spores present in the air.…”
Section: Introductionmentioning
confidence: 99%
“…They are also relevant to other types of instruments. Several bioaerosol detectors measure UV fluorescence from biological particles [14][15][16][17][18][19] . More intense UV excitation generally leads to more intense fluorescence 20 , which is beneficial, but if the excitation is too intense the aerosol particles will be damaged potentially interfering with more selective methods of subsequent analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a number of real-time and commercial instruments including the Ultraviolet Aerodynamic Particle Sizer (UV-APS; TSI Inc., Shoreview, MN, USA) and the Waveband Integrated Bioaerosol Sensor (WIBS; Droplet Measurement Technologies, Longmont, CO, USA) are being commonly used in bioaerosol research communities (e.g., Agranovski et al, 2003;Bhangar et al, 2014;Brosseau et al, 2000;Foot et al, 2008;Huffman et al, 2010;Perring et al, 2015;Stanley et al, 2011;Toprak and Schnaiter, 2013). The main principle common to these techniques is the detection of intrinsic fluorescence from fluorophores such as amino acids, coenzymes, vitamins, and pigments that ubiquitously occur in aerosols of biological origin (e.g., Hill et al, 2009;Pan et al, 2010;Pöhlker et al, 2012Pöhlker et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%